Nonradiologist Physician Comprehension of Artificial Intelligence Utilization in Medical Imaging in Saudi Arabia - Hassan Ali Alsayegh; Yasser Nasser Asiri (Hail Journal of Health Sciences)
Objective: Since the use of AI in radiology has recently improved rapidly and advanced to the implementation phase, health care providers, particularly non-radiologist clinicians, must be aware of the strengths and weaknesses of this technology. Hence, identifying knowledge gaps among nonradiologist clinicians is important for providing solutions. Therefore, this study aimed to identify knowledge gaps regarding the implementation of AI in radiology. Methods: This nationwide online survey targeted certified non-radiologist clinicians in the Kingdom of Saudi Arabia from 1 April to 31 May 2023. It evaluates the knowledge and attitudes of participants regarding AI applications in radiology from different perspectives. Results: In total, 315 participants responded to the survey. More than 40% of participants were younger than 40 years. The majority were residents or consultants. Approximately 54% of participants were unaware of the use of AI in radiology, and most believed that the radiologist bears responsibility for AI-generated reports. Conclusion: The majority of nonradiologist physicians in Saudi Arabia lack knowledge, which necessitates dedicated educational exhibitions aimed at educating physicians concerning legal, medical and technical issues. Gender differences in awareness of AI in radiology were observed. Consultants and residents are comfortable acting on radiology reports, and privacy and security are continually maintained. Most participants were comfortable with the hybrid approach to radiological reporting.